Transgender San Francisco collection. ([Place of publication not identified] : [publisher not identified])
The Transgender San Francisco Collection includes administrative documents, clippings, and conference materials from Transgender San Francisco (TGSF). Founded in 1982 in the Bay Area under the name Educational TV Channel (ETVC), the group was started by a small group of cross-dressing individuals seeking a safe place to meet. ETVC eventually expanded beyond social gatherings, offering members educational seminars and promoting a positive image of transgendered people among the general public. In 1994, ETVC received non-profit status, and the group changed its name to Transgender San Francisco in 1998.
Date range of documents: 1986-1994.
Reproduction of the orignals from the Gay, Lesbian, Bisexual, and Transgender Historical Society.
Keywords: Educational TV Channel (Organization); Transgender people; Cross-dressing.